Efficacy of endophytic bacteria as promising inducers for enhancing the immune responses in tomato plants and managing Rhizoctonia root-rot disease - Mona M. Abbas; Walaa H. Ismael; Amira Y. Mahfouz; Ghadir E. Daigham; Mohamed S. Attia (Scientific Reports, 2024)
Abstract Around the world, a variety of crops, including tomatoes, suffer serious economic losses due to the Rhizoctonia root-rot disease. Herein, Bacillus velezensis, Bacillus megaterium, and Herpaspirillum huttiense isolated from strawberry (Fragaria chiloensis var. ananassa) plants were pragmatic as plant growth promotors for battling the Rhizoctonia root rot disease and bringing about defense mechanisms as well as growth promotional strategies in tomato plants. These endophytic bacteria demonstrated potent antifungal activity against R. solani in vitro along in vivo. Data explained that the isolated endophytic bacteria could produce Indole acetic acid, Gibberellic acid GA, and siderophore as well as solubilize phosphate in the soil. The consortium of (Bacillus velezensis, Bacillus megaterium, and Herpaspirillum huttiense) increased the protection % against Rhizoctonia infection by (79.4%), followed by B. velezensis by (73.52%), H. huttiense by (70.5%), and B. megaterium by (67.64%), respectively. There was an increase in soluble proteins and carbohydrates in infected plants treated with a consortium of endophytic bacteria by 30.7% and 100.2% over untreated infected plants, respectively. Applying endophytic bacteria either alone or in combination lowered the level of malondialdehyde MDA and hydrogen peroxide H2O2 and improved the activities of antioxidant enzymes in both infected and uninfected plants. Also, bacterial endophytes have distinctive reactions regarding the number and concentrations of isozymes in both infected and uninfected plants. It could be recommended the commercial usage of a mixture of targeted bacterial endophyte strains as therapeutic nutrients against Rhizoctonia root-rot disease as well as plant growth inducer.